Pollen, biomarker and stable isotope evidence of late Quaternary environmental change at Lake McKenzie, southeast Queensland - Ataham, P.; Heijnis, H.; Dodson, J.; Grice, Kliti; Le Metayer, Pierre; Taffs, K.; Hembrow, S.; Woltering, Martijn; Zawadzki, A. (Springer Link, 2014)
Unravelling links between climate change and vegetation response during the Quaternary is important if the climate–environment interactions of modern systems are to be fully understood. Using a sediment core from Lake McKenzie, Fraser Island, we reconstruct changes in the lake ecosystem and surrounding vegetation over the last ca. 36.9 cal kyr. Evidence is drawn from multiple sources, including pollen, micro-charcoal, biomarker and stable isotope (C and N) analyses, and is used to gain a better understanding of the nature and timing of past ecological changes that have occurred at the site. The glacial period of the record, from ca. 36.9 to 18.3 cal kyr BP, is characterised by an increased abundance of plants of the aquatic and littoral zone, indicating lower lake water levels. High abundance of biomarkers and microfossils of the colonial green alga Botryococcus occurred at this time and included large variation in individual botryococcene d13C values. A slowing or ceasing of sediment accumulation occurred during the time period from ca. 18.3 to 14.0 cal kyr BP. By around 14.0 cal kyr BP fire activity in the area was reduced, as was abundance of littoral plants and terrestrial herbs, suggesting wetter conditions from that time. The Lake McKenzie pollen record conforms to existing records from Fraser Island by containing evidence of a period of reduced effective precipitation that commenced in the mid-Holocene.